2001
DOI: 10.1073/pnas.161272698
|View full text |Cite
|
Sign up to set email alerts
|

IL-7 differentially regulates cell cycle progression and HIV-1-based vector infection in neonatal and adult CD4+T cells

Abstract: Differences in the immunological reactivity of umbilical cord (UC) and adult peripheral blood (APB) T cells are poorly understood. Here, we show that IL-7, a cytokine involved in lymphoid homeostasis, has distinct regulatory effects on APB and UC lymphocytes. Neither naive nor memory APB CD4 ؉ cells proliferated in response to IL-7, whereas naive UC CD4 ؉ lymphocytes underwent multiple divisions. Nevertheless, both naive and memory IL-7-treated APB T cells progressed into the G1b phase of the cell cycle, albei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
82
2
1

Year Published

2003
2003
2014
2014

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 93 publications
(97 citation statements)
references
References 49 publications
12
82
2
1
Order By: Relevance
“…Our findings suggest that the decreased level of serum IL-7 in the elderly could be responsible for the decreased EM CD4 ϩ T cells. Although the mechanism for the effect of IL-7 on T cells is not fully understood, such an effect is unlikely to be secondary to increased cell proliferation, because IL-7 does not induce the proliferation of naive and memory human CD4 ϩ T cells (13,36). Likewise, we found that IL-7 did not induce the proliferation of human CD4 ϩ T cells (data not shown).…”
Section: Discussionmentioning
confidence: 65%
“…Our findings suggest that the decreased level of serum IL-7 in the elderly could be responsible for the decreased EM CD4 ϩ T cells. Although the mechanism for the effect of IL-7 on T cells is not fully understood, such an effect is unlikely to be secondary to increased cell proliferation, because IL-7 does not induce the proliferation of naive and memory human CD4 ϩ T cells (13,36). Likewise, we found that IL-7 did not induce the proliferation of human CD4 ϩ T cells (data not shown).…”
Section: Discussionmentioning
confidence: 65%
“…Given the profound effects of IL-7 on the survival of human thymocytes, it is possible that IL-7 might prevent or attenuate HIV-mediated destruction of the thymus. However, IL-7 has also been shown to enhance HIV replication and cytopathicity (22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32). Thus, it is unclear whether IL-7 might enhance thymocyte survival in the HIVinfected thymus or, alternatively, enhance HIV-mediated thymocyte destruction.…”
Section: Effects Of Il-7 On Hiv-infected and Uninfected Thymus In Scimentioning
confidence: 99%
“…Nevertheless, the fact that IL-7 has been shown to enhance HIV infection, replication, and cytopathicity (22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32) has raised some concerns regarding its potential use in HIV disease. We sought to identify more specifically the effects of IL-7 on human thymocyte survival and to study the effects of IL-7 on the HIV-infected human thymus.…”
mentioning
confidence: 99%
“…However, it was recently reported that inducing the resting T-cells to enter into the G 1b phase of the cell cycle by stimulation through the T-cell receptor and CD28 co-stimulation receptor, using anti-CD3 plus anti-CD28 antibodies, was sufficient to render the cells susceptible to HIV-1 infection and replication [130]. Moreover, exposing T-cells to cytokines that do not trigger cell division could render them permissive to transduction with HIV-1-vectors [134][135][136]. These findings suggest that partial activation of resting T-cells is sufficient for gene transfer by HIV-1-derived vectors and that DNA synthesis or mitosis of these cells is not necessary.…”
Section: Targeting By Specific Vector-mediated Target Cell Activationmentioning
confidence: 99%